Manajemen Perpustakaan Sekolah Untuk Sumber Belajar Peserta Didik - Mohamad Muspawi; Engla Okta Piana (Universitas Batanghari Jambi, 2018)
This research background of the fact that the author of the initial encounter on the ground that the SDN 13 / I Muarabulian has sought to provide library facilities for learners. But the efforts of the school in providing library services yet provide maximum results. The school library is still rarely visited by students to be used as a learning resource. The purpose of this study was to describe the management of the library as a source for students at SDN 13 / I Muarabulian. This research method is descriptive qualitative research with the principal subject of one person, and one person librarians. The method used in this research is qualitative method. The data collection technique using observation technique, documentation, and interviews. To check the validity of the data, the authors do diligence observation, triangulation, member check, audit trail. And to analyze the data, the authors conducted a review and data reduction, the unitization of data, categorization data, and interpretation of data. The results of this study indicate that the management of the library as a learning resource has not run optimally. Some aspects of library management still has many shortcomings such as building libraries of the schools are still small and narrow and has a size of about 20 square meters with details of length of 5 meters and a width of 4 meters, tools and equipment that is not yet complete, only the wastebasket, stamp library, library stamp and stamp inventory. While supplies libraries owned namely wardrobes, tables, and chairs, room layout library focuses only on the arrangement of tables, chairs study and library, the collection of library materials is still a little in the form of books and non-books and library collections which contains fiction and non-fiction, lack of librarians, the service is still not controlled, and the absence of clear rules library. Based on the research that has been done, it can be concluded that the management of the library as a learning resource has not run optimally because it still has many shortcomings.